Virtual reality simulation in a health assessment laboratory course: a mixed-methods explanatory study examining student satisfaction and self-confidence - Vihos, Jill; Chute, Andrea; Carlson, Susan; Shah, Mamta; Buro, Karen; Velupillai, Nirudika (My University, 2024)
Background: The purpose of this mixed-methods study was to examine the relationship between virtual reality simulation (VRS) and student satisfaction and self-confidence in a health assessment laboratory course. Methods: Second-year students (n = 37) completed a postoperative respiratory distress scenario using Elsevier’s Simulation Learning System with Virtual Reality. All participants completed the Satisfaction and Self-Confidence in Learning Scale; a subset participated in 1:1 semistructured interviews. Results: Satisfaction and self-confidence scores were strongly correlated. VRS experiences of fidelity, communication confidence and competence, learning with peers, integrated learning and critical thinking, and a safe space to learn were related to students’ satisfaction and self-confidence. Conclusions: VRS experiences are correlated with high student satisfaction and self-confidence.
Keywords: health assessment; prelicensure nursing students; simulation design; virtual reality simulation